The Interpretation of the Hadith on the Characteristics of Women and Its Implications for Islamic Law - Yahya, Agusni; Zainuddin, Muslim (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2021)
This study discusses an analysis of the hadith about the characteristics of women and its implications for Islamic law. This article uses a study of the sanad (chain) and matan (wording or contents) of a hadith. It uses the theory of ma'anil hadithor science that discusses the meanings of a hadith, which allows the emergence of a textual and contextual understanding of a hadith. The understanding of a hadith is analyzed from the Islamic law perspective. This study concludes that the sanad (chain) and matan (wording or contents) of this hadith are authentic. The Sanad (chain) is authentic because it continues to the Messenger of Allah, the narrators are fair, dhabit and there is no zyudz or illat found. Nevertheless, this hadith should be understood contextually or symbolically-metaphorically, although there are scholars who understand it textually or literally. The content of the hadith teaches humans that when dealing with women, they should be careful and treat them wisely because their character and nature are like crooked ribs. They should neither be treated harshly because it will break, nor left unnoticed because it will make them go astray. However, the hadith cannot be understood textually because it leads to women subordination; the hadith should be interpreted contextually instead, and by so doing women will be treated equally and fairly. Therefore, it is important to understand this hadith contextually to allow a fair treatment for women and with dignity because it will affect the interpretation of the Islamic law and Islamic teachings in general are maintained.